1979
DOI: 10.1002/anie.197905351
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Metallacycles with Reactive Metal‐Carbon σ Bonds

Abstract: to R = 0.046 We are grateful lo Dr. K. P e r m and Prof. H. GI i'on S Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Crystals of 6 were grown from a saturated pentane solution at −35 °C and analyzed by scXRD (Scheme ). The solid-state structure confirmed that one of the allyl moieties on the tape ligand had been activated, presumably through a transient (and unobserved) [Fe]–H intermediate, possibly via β-(allyl)carbon atom attack, which has been previously documented; related five-membered ring-systems (−MPCH 2 CH 2 CH 2 −) have also been reported. Promiscuity of the tape ligand is further showcased by halide abstraction from 3 , which gives the η 2 -alkene complex, 7  31 P­{ 1 H} NMR signatures at δ P = + 83.0 and −8.3 ppm ( 2 J P–P = 59.6 Hz), in addition to a connectivity map provided by X-ray crystallography, buttress this assignment (Scheme ). …”
Section: Resultssupporting
confidence: 59%
“…Crystals of 6 were grown from a saturated pentane solution at −35 °C and analyzed by scXRD (Scheme ). The solid-state structure confirmed that one of the allyl moieties on the tape ligand had been activated, presumably through a transient (and unobserved) [Fe]–H intermediate, possibly via β-(allyl)carbon atom attack, which has been previously documented; related five-membered ring-systems (−MPCH 2 CH 2 CH 2 −) have also been reported. Promiscuity of the tape ligand is further showcased by halide abstraction from 3 , which gives the η 2 -alkene complex, 7  31 P­{ 1 H} NMR signatures at δ P = + 83.0 and −8.3 ppm ( 2 J P–P = 59.6 Hz), in addition to a connectivity map provided by X-ray crystallography, buttress this assignment (Scheme ). …”
Section: Resultssupporting
confidence: 59%
“…464 - 480 We know of no reports for technetium in this category. The chemistry of rhenium is both interesting and varied although it represents only a small part of this area which has seen rapid growth in the last few years.…”
Section: Metallocyclic Derivatives Containing Carbon To Metal Bond(s)mentioning
confidence: 99%
“…477 Two series of metallo-alicyclic derivatives are obtained in the reaction of [Re{P(O)R 2 j(CO) 4 ]2~ with (CH 2 ) W (CH 2 OS(O) 2 CF 3 ) 2 (n = 1 or 2) 478 ' 479 or in the reaction of [ReBr(CO) 5 ] with Ph 2 P(CH 2 ) n MgBr (« = 3 or 4). 480 These five-and six-membered metallocycles engage in SO 2 and CO insertions, 290 ' 480 (see also Section 30.6.6). For the latter, assistance of Al 2 Br 6 is required which yields the adduct (91); hydrolysis of this intermediate gives the acyl product listed next to it in Table 14.…”
Section: Metallocyclic Derivatives Containing Carbon To Metal Bond(s)mentioning
confidence: 99%